Association of serum uric acid-to-high-density lipoprotein cholesterol ratio with cardiovascular disease risk in patients with metabolic dysfunction-associated fatty liver disease: a cross-sectional NHANES analysis - Wang, Xianyao; Shi, Yuchen; Zi, Ying; Long, Jun; Shi, Rongjie (Frontiers in Nutrition, 2025)
ObjectiveThe relationship between the serum uric acid-to-high-density lipoprotein cholesterol ratio (UHR) and cardiovascular disease (CVD) risk in patients with metabolic dysfunction-associated fatty liver disease (MAFLD) is unknown. This study aims to investigate the relationship between UHR and cardiovascular disease risk in patients with MAFLD.MethodsData for this study were obtained from the National Health and Nutrition Examination Survey (NHANES) 2017–2020, in which 3289 patients with MAFLD participated. Participants were grouped according to their 10-year cardiovascular disease risk level, which was assessed by the Framingham Risk Score (FRS). We used binary logistic regression to analyze the relationship between UHR and CVD risk and smoothed curve-fitting models and threshold effect analyses to describe the relationship between UHR and CVD risk scores.ResultsAfter adjusting for all confounders, individuals with high UHR exhibited a higher prevalence of intermediate/high risk by FRS [odds ratio (OR): 2.12, 95% confidence interval (CI): (1.34, 3.35), P = 0.001]. UHR was nonlinear positive correlated with FRS (log-likelihood ratio test < 0.001). And there was a breakpoint of 364.38 and an apparent threshold effect. When UHR was lower than 364.38, The FRS increased with increasing UHR (P < 0.0001), whereas when UHR was higher than 364.38, the relationship between FRS and UHR was statistically insignificant (P = 0.0964).ConclusionThe UHR was significantly associated with a 10-year risk of cardiovascular disease in patients with MAFLD. Higher UHR was associated with higher FRS in patients with MAFLD. The UHR can be a valid biomarker for predicting the 10-year risk of cardiovascular disease in patients with MAFLD.